Decreased 11β‐hydroxysteroid dehydrogenase 1 in lungs of steroid receptor coactivator (Src)‐1/‐2 double‐deficient fetal mice is caused by impaired glucocorticoid and cytokine signaling. Issue 12 (18th October 2020) - Chen, Jingfei; Mishra, Ritu; Yu, Yaqin; McDonald, Jeffrey G.; Eckert, Kaitlyn M.; Gao, Lu; Mendelson, Carole R.
Abstract: Our previous research revealed that steroid receptor coactivators (Src)‐1 and ‐2 serve a critical cooperative role in production of parturition signals, surfactant protein A and platelet‐activating factor, by the developing mouse fetal lung (MFL). To identify the global landscape of genes in MFL affected by Src‐1/‐2 double‐deficiency, we conducted RNA‐seq analysis of lungs from 18.5 days post‐coitum (dpc) Src‐1 −/− /‐2 −/− (dKO) vs . WT fetuses. One of the genes most highly downregulated (~4.8 fold) in Src‐1/‐2 dKO fetal lungs encodes 11β‐hydroxysteroid dehydrogenase type 1 (11β‐HSD1), which catalyzes conversion of inactive 11‐dehydrocorticosterone to the glucocorticoid receptor (GR) ligand, corticosterone. Glucocorticoids were reported to upregulate 11β‐HSD1 expression in various cell types via induction of C/EBP transcription factors. We observed that C/ebpα and C/ebpβ mRNA and protein were markedly reduced in Src‐1/‐2 double‐deficient ( Src‐1/‐2 d/d ) fetal lungs, compared to WT. Moreover, glucocorticoid induction of 11β‐hsd1, C/ebpα and C/ebpβ in cultured MFL epithelial cells was prevented by the SRC family inhibitor, SI‐2. Cytokines also contribute to the induction of 11β‐HSD1. Expression of IL‐1β and TNFα, which dramatically increased toward term in lungs of WT fetuses, was markedly reduced in Src‐1/‐2 d/d fetal lungs. Our collective findings suggest that impaired lung development and surfactant synthesis in Src‐1/‐2 d/d fetuses are likely caused, in part, by decreased GR and cytokine induction of C/EBP and NF‐κB transcription factors. This results in reduced 11β‐HSD1 expression and glucocorticoid signaling within the fetal lung, causing a break in the glucocorticoid‐induced positive feedforward loop.